2018
DOI: 10.1111/emre.12303
|View full text |Cite
|
Sign up to set email alerts
|

The Proactive Initiation of SMEs’ Foreign Business Relationships

Abstract: Taking control over one's destiny by proactive internationalization has been considered an important performance indicator in small business research. We develop a model that examines how internal and external contextual factors influence SMEs’ foreign market entry through proactive initiation of business relationships in foreign markets. The ability to proactively leverage such relationships is essential for opening up avenues into foreign markets and serves as a first step in negating the liability of outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 99 publications
(197 reference statements)
2
23
0
2
Order By: Relevance
“…In turn, these resources (e.g., information and knowledge) contribute to their firms' performance. Our findings also favor Tolstoy (2018) who claimed that proactive managers enter into a new market before their competitors' arrival and seize all the essential resources to ensure their firms' growth.…”
Section: Discussionsupporting
confidence: 52%
“…In turn, these resources (e.g., information and knowledge) contribute to their firms' performance. Our findings also favor Tolstoy (2018) who claimed that proactive managers enter into a new market before their competitors' arrival and seize all the essential resources to ensure their firms' growth.…”
Section: Discussionsupporting
confidence: 52%
“…Knight [49] proved that this three-dimensional concept is the main factor of success, determining the international accomplishments of firms. The positive relation between entrepreneurial orientation and the internationalization process was observed in numerous empirical works [19,33,52,57,58]. Very few researchers reported an insignificant relation between entrepreneurial orientation and internationalization [59] or indicated a negative relation between the two factors [60].…”
Section: Entrepreneurial Orientation and Internationalizationmentioning
confidence: 90%
“…To date, some researchers have investigated how EO impacts firm performance (e.g., [16][17][18]) or internationalization (e.g., [19][20][21][22][23]), while other researchers have found some empirical evidence that the knowledge management process (knowledge acquisition, sharing, and utilization) impacts the internationalization of a firm [24][25][26][27][28][29][30][31]. The effects of knowledge of internationalization and the effects of entrepreneurial orientation on internationalization have been discussed independently by previous researchers such as Etemad [19], Hsu, Chen and Chen [32], Tolstoy [33], and Yoon, Kim, and Dedahanov [34].…”
Section: Introductionmentioning
confidence: 99%
“…Rant and Černe (2017) observed that differentiation via innovation positively impacts firm performance on international markets in the case of firms from the region of CEE. Numerous studies confirm a positive relation between entrepreneurial orientation and the internationalisation process (Florida, 1997;Yiu, Lau, & Bruton, 2007;Etemad, 2015;Swoboda & Olejnik, 2016;Tolstoy, 2018). However, this is not the final position of the researchers.…”
Section: Literature Reviewmentioning
confidence: 97%